2008
DOI: 10.1037/a0013302
|View full text |Cite
|
Sign up to set email alerts
|

Me against myself: Motivational conflicts and emotional development in adulthood.

Abstract: Two studies investigated adult age differences in the frequency and emotional consequences of motivational conflicts (i.e., feeling that one wants to or should do something else in a given situation). Study 1 compared younger and older adults. Study 2 included a more age-heterogeneous sample ranging from 20 to 70 years. Data were obtained using diary and experience-sampling methods. Multilevel regression showed that motivational conflict was associated with lower emotional well-being. With age, the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 49 publications
(50 reference statements)
9
81
0
1
Order By: Relevance
“…This interest arose from the idea that one can better understand why individuals of different ages feel different in their everyday lives when one knows whether they differ in how they want to feel. Consistent with evidence from other studies (e.g., Carstensen et al, 2000;Riediger & Freund, 2008), our findings revealed an age-related increase in day-to-day emotional well-being. These age differences largely corresponded to differences in how people wanted to influence their feelings.…”
Section: Discussionsupporting
confidence: 82%
“…This interest arose from the idea that one can better understand why individuals of different ages feel different in their everyday lives when one knows whether they differ in how they want to feel. Consistent with evidence from other studies (e.g., Carstensen et al, 2000;Riediger & Freund, 2008), our findings revealed an age-related increase in day-to-day emotional well-being. These age differences largely corresponded to differences in how people wanted to influence their feelings.…”
Section: Discussionsupporting
confidence: 82%
“…This can be done with experience or time sampling procedures that allow tapping into the everyday lives of (groups of) participants in a relatively unobtrusive way. This approach seems very promising when dealing with the ecologies of different age groups (e.g., Riediger & Freund, 2008). In this way, stimuli that are equivalent across age groups and representative of the ecologies of the different age groups can be identified.…”
Section: )mentioning
confidence: 99%
“…This might or might not compromise subjective wellbeing. On the one hand, previous studies have shown that goal conflict can have adverse consequences for subjective well-being (e.g., Riediger & Freund, 2008) and psychosomatic health (e.g., Freund, Knecht, & Wiese, 2014). On the other hand, avoiding goal conflict by disengaging from goals can be negative from a control theoretical perspective (e.g., Carver & Scheier, 1990) as it deprives the individual from the potential benefits of goal striving and eventual goal attainment.…”
Section: Current Research On Multiple Goalsmentioning
confidence: 91%
“…For instance, individuals can negotiate multiple goals by employing strategies of concurrent or strategies of sequential goal pursuit (Orehek & Vazeou-Nieuwenhuis, 2013). Concurrent strategies usually comprise using single multifinal means to purse multiple goals at the same time (Köpetz, Faber, 274 TOMASIK Fishbach, & Kruglanski, 2011), whereas sequential strategies require prioritizing the allocation of one's resources to one goal at a time (Riediger & Freund, 2008).…”
Section: Strategies Of Adaptive Goal Pursuitmentioning
confidence: 99%